The Impact of Minimarket Existence towards Small Vendors Welfare - Tyas Eko Raharjo (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
This research is related to the impact of minimarket toward future existence of small vendors, is done to describe small vendors welfare living around minimarket. Respondents in this research are small vendors selling their commodities around minimarkets. Data are gathered through interview, observasion, and documentary analysis, and analysed through qualitatif descriptive technique. The result shows that small vendors having various degree of welfare, depending on the commodities they sell vendors experience a reduce in their clients since there is minimarket, even they are almost bankkrupt for their low ability to compete with minimarket, but small vendors that sell food and drink nearby minimarket feel profitable. It can be concluded that some small vendors feel negative effect nad some feel positive effect with the existenceof minimarket nearby them. It depends on the commodities they sell vendors feel negative because the commodities they sell can be found in minimarket, while food and drink vendors having positive chance bcause the commodites can not be found in minimarket.